The Manila City Bahay Pag-asa changing the image of of BPA shelters for children in conflict with the law through architecture - Rosales, Karina O. (College of Architecture, University of the Philippines Diliman, 2020)
Juveniles who commit criminal acts, recognized by the law as "children in conflict with the law", have long been an alarming problem in the Philippines. These children are apprehended and brought into facilities known as "Bahay Pag-asa" for the purpose of providing temporary residential care, while incorporating rehabilitation methods into the process at the same time. These BPA shelters should ideally serve as houses of hope for CICLs. However, reports in recent years show that those goals are not being achieved. With substandard design, resources, and manpower, most BPAs have ironically become breeding grounds of abuse and neglect, increasing further the number of recidivists and unsuccessfully rehabilitating the children. This has caused the Bahay Pag-asa to be seen in a negative light both by the public and by CICLs as an unwanted "child prison" which they would want to escape from. This thesis proposes the use of architecture as a means to change that kind of negative image by designing the new Manila City Bahay Pag-asa. The design of the Manila City BPA aims to implement rehabilitation by creating zones with varying levels of privacy and security, while giving CICLs and other users the opportunity to freely bond with each other and further strengthen their relationships with each other, it also integrates a family-centered framework by providing spaces that allow for family sessions, counseling and interactions.